How journalist in Ireland perceive the challenge of misinformation - Blanco-Ruiz, Sonia María; Palomo-Torres, María Bella (My University, 2020)
The arrival of the Internet has entailed a radical transformation in the world of journalism, not only in its form of production, but also in its distribution and reception. Nowadays the audience receives information from traditional media, but equally from many other actors such as technology companies that publish all types of content on social networks (Facebook, Google, Twitter….). Even though these sites are not governed by journalistic standards or criteria some authors are considering them as news mediums (Levinson, 2019). In addition, 57% of young people aged 18-24 have their first contact with the news every day through social media (Newman et al., 2019), making them more vulnerable to fake new considering that “...false news spreads faster, deeper and more broadly than the truth” (Vosoughi et al., 2018) In this new hybrid scenario (Chadwick, 2017) it is worth wondering what kind of strategies or new productions routines are the media approaching to fight against fake news and disinformation in western countries. Ireland trust level in news is 48% (Newman et al., 2019, p. 96), high enough to carry out an ethnographic study in two of its main media: a traditional one with its web version: The Independent, and a digital native one: TheJournal.ie This exploratory research analyses Irish journalists' perception of misinformation disorder, through six in-depth interviews with editors, reporters and social media managers. In addition, observation periods have been carried out in both newsrooms during november and december 2019, to determine their daily routines. Results indicate that misinformation in Ireland is not as pressing a problem as in countries with a larger and therefore more competitive media ecosystem. One of the reasons given by the interviewees is strict monitoring of journalistic criteria, including the double and triple contrast of information, and absolute confidence in sources and collaborators.
Keywords: Ciberterrorismo; Periodismo; Medios de comunicación social; Irlanda; Redes sociales en internet; Disinformation; Fake News; Ireland; Journalism; Misinformation; Social Media